Process optimization for manufacturing process using machine learning approach - Wu, Jiaze (Nanyang Technological University, 2022)
In manufacturing processes, sensors are often implemented to collect data and achieve defect detection. To establish correlation between collected data and quality measurements, machine learning methods are widely used. However, when a new process is developed, it often require sufficient data instances for training to build a model with high accuracy, which costs time and resources.